Letter: budesonide for functional dyspepsia with duodenal eosinophilia—randomised, double‐blind, placebo‐controlled parallel‐group trial. Issue 12 (24th May 2021) - Talley, N.J.; Walker, M.M.; Jones, M.; Keely, S.; Koloski, N.; Cameron, R.; Fairlie, T.; Burns, G.; Shah, A.; Hansen, T.; Harris, G.; Holtmann, G.
LINKED CONTENT: This article is linked to Ronkainen et al paper. To view this article, visit https://doi.org/10.1111/apt.15308